2022
DOI: 10.1155/2022/2329952
|View full text |Cite|
|
Sign up to set email alerts
|

Innovative Research on Teaching Method of Taekwondo in College Elective Courses under the Background of Big Data

Abstract: In the new stage of the new century, a new technological revolution is coming quietly. This revolution is represented by “data.” The application of “big data (B D A)” technology is causing changes in all walks of life, and the use of “B D A research methods” in the education field will inevitably become a trend. The purpose of this article is an innovative research on the teaching methods of Taekwondo based on the background of B D A in a college elective course. This paper first introduces the core technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The core of Taekwondo teaching and competition is the practical evaluation of movement completion quality [3]. In the Taekwondo Poomsae competition, movement completion quality significantly impacts the final score [4]. As an essential basic skill, Taekwondo Poomsae plays a pivotal role in Taekwondo learning [5].…”
Section: Introductionmentioning
confidence: 99%
“…The core of Taekwondo teaching and competition is the practical evaluation of movement completion quality [3]. In the Taekwondo Poomsae competition, movement completion quality significantly impacts the final score [4]. As an essential basic skill, Taekwondo Poomsae plays a pivotal role in Taekwondo learning [5].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%